Discrepancies in Identification of Left Atrial Enlargement Using Left Atrial Volume versus Left Atrial‐to‐Aortic Root Ratio in Dogs. (23rd July 2014) - Wesselowski, S.; Borgarelli, M.; Bello, N.M.; Abbott, J.
<x xml:space="preserve">Abstract</x> Background Left atrial size is prognostically important in dogs with myxomatous mitral valve disease (MMVD). Hypothesis/Objectives To compare the level of agreement in identification of left atrial enlargement (LAE) between the left atrial‐to‐aortic root ratio (LA : Ao) and left atrial volume using the biplane area‐length method indexed to body weight (LA Vol/BW). Animals Sixty dogs with MMVD and 22 normal dogs were prospectively studied with 2‐dimensional echocardiography. Methods The upper limit of normal for LA Vol/BW was defined as 1.1 mL/kg. LA : Ao was deemed normal if ≤1.5. To define overall disease severity, each dog was assigned a mitral regurgitation severity score (MRSS) based on echocardiographic parameters that did not include left atrial size. ACVIM staging also was utilized. Results Of 60 affected dogs, 20 were ACVIM Stage B1, 25 were Stage B2, and 15 were Stage C. LA Vol/BW identified LAE in 12 cases in which LA : Ao was normal; 7 of these were Stage B1 and 5 were Stage B2. This diagnostic disagreement was significant (P = .00012). Of the 12 cases in which diagnostic discrepancies were identified, 5/5 of the B2 dogs and 3/7 B1 dogs had a moderate MRSS, whereas 4/7 B1 dogs had a mild MRSS. No diagnostic discrepancies between LA : Ao and LA Vol/BW were apparent in dogs with a severe MRSS. Conclusions and Clinical Importance This study shows evidence of diagnostic disagreement between LA : Ao and LA Vol/BW for assessment of LAE. LA Vol/BW may be superior to LA : Ao for identification of mild LAE.